Analisis Keterampilan Menggunting pada Anak Usia Dini di TK Ki Hajar Dewantoro V - Ananda Tasya Isami; Virgina Cahyani; Pratiwi Monoarfa; Nurnaningsi Djibu; Annisa Fahmi Mannassai (Institut Nalanda, 2025)
Cutting skills are one of the fine motor skills that are important in early childhood development. This activity not only involves eye-hand coordination, but also supports children's cognitive, social, and emotional development. This study aims to analyze the level of cutting skills of early childhood children in Ki Hajar Dewantoro V Kindergarten, using a quantitative descriptive approach. Data were collected through a skill assessment checklist that included indicators of accuracy, neatness, speed, and eye-hand coordination. The results showed that 58.82% of children had optimal skills, while 23.53% were in the low category. Variations in these abilities are influenced by age factors, environmental support, and children's self-confidence levels. These findings are in line with Vygotsky and Erikson's developmental theories, which emphasize the importance of scaffolding and emotional support in skill development. This study concludes that cutting activities can be an effective method to improve children's fine motor skills, especially if supported by the right learning approach and intensive guidance.